2004
DOI: 10.1007/bf03018425
|View full text |Cite
|
Sign up to set email alerts
|

L’administration intrathécale de lidocaïne et de sufentanil diminue le temps de récupération après une opération du rectum en chirurgie ambulatoire

Abstract: P Pu ur rp po os se e: : A short recovery time for same day surgery is important to the patient and the hospital. A prospective, randomized, doubleblinded study in the postanesthetic care unit was designed to compare the recovery time from spinal anesthesia with low-dose intrathecal (IT) lidocaine and sufentanil to that with IT lidocaine alone. The incidence of adverse effects was also assessed.M Me et th ho od ds s: : Forty-nine patients (ASA I-III, age 20-69 yr) underwent spinal anesthesia for rectal surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In the present study, we asked patients specifically about itching and the incidence of this adverse event in patients exposed to IT sufentanil was approximately 80%, in contrast to 50% in a similar study 4 by our group. However, the two studies may not be entirely comparable because the explanations given to the patients were different.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 71%
See 2 more Smart Citations
“…In the present study, we asked patients specifically about itching and the incidence of this adverse event in patients exposed to IT sufentanil was approximately 80%, in contrast to 50% in a similar study 4 by our group. However, the two studies may not be entirely comparable because the explanations given to the patients were different.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 71%
“…In the present study, patients were told that the main purpose of the trial was to test whether ondansetron would prevent itching after spinal anesthesia with lowdose lidocaine and IT sufentanil. In our previous study, 4 patients were told that the main purpose of the study was to compare recovery after two different techniques for spinal anesthesia, warning about possible complications including pruritus. Since pruritus is a sensation, 2,3 its perception may also be influenced by the explanation of the project to the patients.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 99%
See 1 more Smart Citation
“…Beverly Waxleretal reported itching as a well-known side effect of intrathecal narcotics. 10 Incidence of pruritus was 56% with sufentanil and lignocaine in their study. No respiratory depression was observed.…”
Section: Parametermentioning
confidence: 70%
“…8,9 Waxler et al reported shorter time to ambulation in patients who received intrathecal lignocaine and sufentanil. 10 Lau et al also reported earlier discharge of outpatients on lignocaine and sufentanil who underwent extracorporeal shock wave lithotripsy. 11 Similar results were observed in our study with significant decrease in ambulation time.…”
Section: Parametermentioning
confidence: 96%